2022
DOI: 10.3389/fgene.2021.773534
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants and Protein Alterations of Selenium- and T-2 Toxin-Responsive Genes Are Associated With Chondrocytic Damage in Endemic Osteoarthropathy

Abstract: The mechanism of environmental factors in Kashin–Beck disease (KBD) remains unknown. We aimed to identify single nucleotide polymorphisms (SNPs) and protein alterations of selenium- and T-2 toxin–responsive genes to provide new evidence of chondrocytic damage in KBD. This study sampled the cubital venous blood of 258 subjects including 129 sex-matched KBD patients and 129 healthy controls for SNP detection. We applied an additive model, a dominant model, and a recessive model to identify significant SNPs. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…For instance, T-2 toxin is implicated in tibial dyschondroplasia ( TD ), which is characterized by the accumulation of immature, poorly differentiated, unmineralized, and avascular cartilage owing to intoxication and growth retardation of long bones in chickens ( Nascimento et al, 2001 ; He et al, 2012 ). Furthermore, T-2 toxin participates in the pathological process of human Kashin-Beck disease ( KBD ) with chondrocyte damage to bone formation and morphogenesis (proliferation, differentiation, migration, and apoptosis) and imbalanced extracellular matrix ( ECM ) homeostasis (inhibition of synthesis and increase in degradation) ( Li et al, 2016 ; Chang et al, 2017 ; Ning et al, 2021 ). Similarly, compared to the control, 2.0 mg/kg of T-2 toxin significantly inhibited the growth and development of tibia in goslings, reducing their length and weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, T-2 toxin is implicated in tibial dyschondroplasia ( TD ), which is characterized by the accumulation of immature, poorly differentiated, unmineralized, and avascular cartilage owing to intoxication and growth retardation of long bones in chickens ( Nascimento et al, 2001 ; He et al, 2012 ). Furthermore, T-2 toxin participates in the pathological process of human Kashin-Beck disease ( KBD ) with chondrocyte damage to bone formation and morphogenesis (proliferation, differentiation, migration, and apoptosis) and imbalanced extracellular matrix ( ECM ) homeostasis (inhibition of synthesis and increase in degradation) ( Li et al, 2016 ; Chang et al, 2017 ; Ning et al, 2021 ). Similarly, compared to the control, 2.0 mg/kg of T-2 toxin significantly inhibited the growth and development of tibia in goslings, reducing their length and weight.…”
Section: Discussionmentioning
confidence: 99%
“…T-2 toxin also reduces DNA synthesis in chondrocytes because of a basic depression of protein, DNA, and RNA ( Wright Jr et al, 1987 ; Sokolović et al, 2008 ; He et al, 2012 ). Furthermore, T-2 toxin facilitates growth retardation and anomalous structural lesions of the TGP, with some unusual apoptotic and necrotic areas interfering with normal proliferation, differentiation, migration, mineralization of chondrocytes and synthesis, degradation of ECM, and the specific molecular expression mechanism ( Ning et al, 2021 ). In addition, inflammatory cytokines (mainly interleukin 1β) potently induce matrix degrading enzyme MMP expression in chondrocytes, inhibit the expression of matrix components, and evoke cell apoptosis, affecting chondrocyte growth under T-2 toxin exposure ( Chang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The significantly upregulated expression of CCNG1 in the deep zone of articular cartilage in KBD patients suggests that CCNG1 may accelerate the chondrocyte necrosis of deep cartilage induced by damage factors. Our previous research found that low selenium status and T-2 toxin exposure can affect the gene and protein expression levels of PPARG, and its SNP rs12629751 is associated with KBD ( Ning et al, 2021 ). PPARG ligands influence the activities of CCNG1, CDK1, GADD45β, CCNA1 and ATM proteins, which are involved in the LPS-triggered expression of genes controlling the DNA damage response ( Mierzejewski et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor gamma (PPARG) is a nuclear receptor and involved in insulin sensitivity and energy metabolism. A recent study demonstrated that genetic polymorphisms of PPARG might promote the risk of the Kashin-Beck disease via disturbing ECM homeostasis [ 39 ]. Mitogen-activated protein kinase 1 (MAPK1) is a subfamily of the MAPK family that regulated a variety of cellular activities.…”
Section: Discussionmentioning
confidence: 99%